Strategy and geopolitics : understanding global complexity in a turbulent world - Rosenberg, Michael (Economist) (Emerald Publishing Limited, 2017)
Large western companies are accelerating their expansion into emerging economies, while relying on oversimplified frameworks to make decisions and complex matrix organizations to make things happen. When critical events do happen (such as terrorist attacks or civil wars), senior executives and the companies they lead are often taken by surprise. As the world shifts to a less stable geopolitical structure, only firms that can acquire a better capability to foresee and prepare for change will prevail over the long term.Strategy and Geopolitics provides a strategic framework that can help senior business executives address the challenges of globalization in this evolving geopolitical landscape. This book underlines the need to go beyond a simplistic understanding of different countries and territories: it discusses the geopolitical issues that can be the cause of success or failure in different markets; and it explores strategies for dealing with global and local complexity, as well as introducing innovative ideas on recruitment and organization.
Includes index.
Keywords: International business enterprises -- Management.; Strategic planning.; Geopolitics -- Economic aspects.; International business.; elektronické knihy; electronic books